A Molecular Ferroelectric Thin Film of Imidazolium Perchlorate That Shows Superior Electromechanical Coupling. Issue 20 (1st April 2014) - Zhang, Yi; Liu, Yuanming; Ye, Heng‐Yun; Fu, Da‐Wei; Gao, Wenxiu; Ma, He; Liu, Zhiguo; Liu, Yunya; Zhang, Wen; Li, Jiangyu; Yuan, Guo‐Liang; Xiong, Ren‐Gen
Abstract: Molecular ferroelectric thin films are highly desirable for their easy and environmentally friendly processing, light weight, and mechanical flexibility. A thin film of imidazolium perchlorate processed from aqueous solution is an excellent molecular ferroelectric with high spontaneous polarization, high Curie temperature, low coercivity, and superior electromechanical coupling. These attributes make it a molecular alternative to perovskite ferroelectric films in sensing, actuation, data storage, electro‐optics, and molecular/flexible electronics. Abstract : Molecular ferroelectric thin films and block crystals along crystal face (10$\bar 2$ ) of imidazolium perchlorate display perfect hexagonal domains similar to that of the trigonal crystal system LiNbO3 . The high spontaneous polarization, high Curie temperature, low coercivity, and superior electromechanical coupling make it a molecular alternative to perovskite ferroelectric films.